Hubungan Pola Asuh Orang Tua Dengan Kejadian Sibling Rivalry di Praktek Bidan Sri Rahayu Kecamatan Wampu Kabupaten Langkat Tahun 2023 - Wan Novita Ulfa Sari; Asnita Sinaga (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2024)
Family is the first environment that has a deep influence on children. Therefore, whether directly or indirectly, the family will be the first place for a child to gain experience and education that can influence his development both physically and psychologically. Education for families, especially children, is a very important thing to pay attention to. Adolescence is a period in the span of human life. During this period, individuals will experience a transition from childhood to adulthood which is accompanied by changes in life. The changes that occur include biological, psychological, social and emotional aspects. This is in line with the opinion of Santrock (2007) who states that adolescence is a period of developmental transition between childhood and adulthood which involves biological, cognitive and socio-emotional changes. Sibling rivalry is a pattern of relationships between siblings that can have both positive and negative impacts. The positive impacts that emerge can be in the form of increased learning motivation, the emergence of affection and understanding between siblings. Meanwhile, the negative impact that appears is solitary behavior and crying. According to research conducted by McNerney. A., & Usner (2014) which was carried out at each life span between the ages of 0-5 years, 5-10 years, 10-15 years, 15-20 years, and 20-25 years obtained results showing that ages 10-15 year has the highest level of sibling rivalry. This is also supported by the opinion of Hurlock (2007) that adolescence is a phase full of conflict and conflict, including with siblings.